LTBP4 genotype predicts age of ambulatory loss in duchenne muscular dystrophy - Flanigan, Kevin M.; Ceco, Ermelinda; Lamar, Kay-Marie; Kaminoh, Yuuki; Dunn, Diane M.; Mendell, Jerry R.; King, Wendy M.; Pestronk, Alan; Florence, Julaine M.; Mathews, Katherine D.; Finkel, Richard S.; Swoboda, Kathryn J.; et al. (Annals of neurology, 2013)
Objective Duchenne muscular dystrophy (DMD) displays a clinical range that is not fully explained by the primary DMD mutations. Ltbp4, encoding latent transforming growth factor‐β binding protein 4, was previously discovered in a genome‐wide scan as a modifier of murine muscular dystrophy. We sought to determine whether LTBP4 genotype influenced DMD severity in a large patient cohort. Methods We analyzed nonsynonymous single nucleotide polymorphisms (SNPs) from human LTBP4 in 254 nonambulatory subjects with known DMD mutations. These SNPs, V194I, T787A, T820A, and T1140M, form the VTTT and IAAM LTBP4 haplotypes. Results Individuals homozygous for the IAAM LTBP4 haplotype remained ambulatory significantly longer than those heterozygous or homozygous for the VTTT haplotype. Glucocorticoid‐treated patients who were IAAM homozygotes lost ambulation at 12.5 ± 3.3 years compared to 10.7 ± 2.1 years for treated VTTT heterozygotes or homozygotes. IAAM fibroblasts exposed to transforming growth factor (TGF) β displayed reduced phospho‐SMAD signaling compared to VTTT fibroblasts, consistent with LTBP4' role as a regulator of TGFβ. Interpretation LTBP4 haplotype influences age at loss of ambulation, and should be considered in the management of DMD patients. ANN NEUROL 2013;73:481–488